Pengembangan Media Simulasi Fisika Berbasis TPACK Pada Materi Hukum Newton - Alfi, Syamiah; Tralisno, Agung (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2025)
The integration of technology in physics education is not yet common. The absence of engaging and interactive physics resources may lead to a decline in students' enthusiasm and understanding of the subject matter being taught. To address this issue, simulation tools for physics learning have been created. This study aims to design effective simulation resources for physics education that align with TPACK principles. The ADDIE model is employed for the development process. A questionnaire is utilized to gather feedback on the validity from material and media experts, as well as from students. The analysis of the data utilizes both quantitative and qualitative methods. The evaluations from material and media experts yielded scores of 94% and 92%, indicating that these resources are highly suitable for educational purposes. Additionally, student feedback revealed that 83.4% categorized their responses as very positive. Therefore, it can be concluded that the physics simulation media centered on Newton's Laws effectively supports TPACK-driven learning in educational settings